2020
DOI: 10.3389/fmolb.2020.00175
|View full text |Cite
|
Sign up to set email alerts
|

The Sequence and Three-Dimensional Structure Characterization of Snake Venom Phospholipases B

Abstract: Snake venom phospholipases B (SVPLBs) are the least studied enzymes. They constitute about 1% of Bothrops crude venoms, however, in other snake venoms, it is present in less than 1%. These enzymes are considered the most potent hemolytic agent in the venom. Currently, no structural information is available about these enzymes from snake venom. To better understand its three-dimensional structure and mechanisms of envenomation, the current work describes the first model-based structure report of this enzyme fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…This protein family was present in 30% of species and had a mean abundance of 0.5% and a maximum of 3%. They have a molecular mass of 35 to 55 kDa (Bernheimer et al 1987;Ullah and Masood 2020). There have been limited investigations into this protein family, and their function and role in human envenomation is unclear.…”
Section: Phospholipase B (Plb)mentioning
confidence: 99%
“…This protein family was present in 30% of species and had a mean abundance of 0.5% and a maximum of 3%. They have a molecular mass of 35 to 55 kDa (Bernheimer et al 1987;Ullah and Masood 2020). There have been limited investigations into this protein family, and their function and role in human envenomation is unclear.…”
Section: Phospholipase B (Plb)mentioning
confidence: 99%
“…The MDMoby and MDweb programs (Hospital et al, 2012), GROMACS (Berendsen et al, 1995), AMBER16 (Case et al, 2005;Maier et al, 2015) were used for Molecular Dynamic Simulation as described previously (Ullah et al, 2019;Ullah and Masood, 2020). The all-atom-protein interaction was found out using FF14SB force field (Darden et al, 1993).…”
Section: Molecular Dynamic Simulationmentioning
confidence: 99%
“…Such studies have shown that the presence and abundance of certain phospholipids in the cell membrane composition could be responsible for increased sensitivity to lysis [22] , [42] . This might be associated to the differential preferences that Phospholipases D (PLDs) exhibit for phospholipid targets [25] , [43] . Upon substrate cleavage, phospholipases produce membrane injury and consequently, provoke the remodelling of the membrane structure [44] , lipid raft formation [45] , and produce inflammatory mediators responsible for cell recruitment, cell death and fibrosis [3] .…”
Section: Discussionmentioning
confidence: 99%